Specifics of material handling for last mile delivery - Šourek, David; Seidlová, Andrea (Kaunas University of Technology, 2024)
The article analyses the limiting factors for material handling for last mile delivery based on the mode of transport. Material handling during last-mile deliveries has its own specifics, which can fundamentally influence the selection of suitable handling equipment, handling units, means of transport and technology. This is mainly manual handling, which often takes place in limited spatial conditions and with various traffic restrictions, such as entrance restrictions or pedestrian zones. These factors can be particularly limiting for vans, which are used most often for last-mile delivery. Cargo bikes are a suitable alternative, but they are not yet very widespread in the Czech Republic. Using the example of the city of Pardubice, the critical places for this manipulation will be defined using the GIS system and the possibilities of using vans and cargo bikes will be compared.
Specifika manipulace s materiálem při dodávkách na poslední míli
Keywords: last mile delivery; cargo bikes, delivery vans; dodávky na poslední míli, nákladní kola, doručovací vozidla